Implementation of Robotics as a Modern Trend in STEM Education - Morze, Nataliia; Strutynska, Oksana; Umryk, Mariia (International Journal of Research in E-learning, 2018)
The paper is devoted to the issues of implementation of STEM education in the learning process of educational institutions. The authors analyse the development of STEM education in Ukraine, determine the level of readiness of educators for understanding the principles of STEM education, and substantiate the need for the introduction of robotics into the educational process as a modern and important trend in STEM education. The concept of educational robotics is analysed. This makes it possible to identify the technical inclinations of students (at an early stage) and development of these inclinations, as well as formation of STEM competency in general. The study focuses on the interdisciplinary aspect of STEM education, in particular on the implementation of interdisciplinary links between STEM subjects and robotics in the conduction process of research and training projects. The authors provide examples of the implementation of robotics in the educational process based on the use of a project method. The article also includes a description of the project for the creation of the Juno Rover robot based on the Arduino robotic platform in university education and two examples of the robotics projects in school education (one of them is implemented on an open platform with freely distributed materials for creating and using 3D printed robots).